A new practical isobaric interference correction model for the in situ Hf isotopic analysis using laser ablation-multi-collector-ICP-mass spectrometry of zircons with high Yb/Hf ratios. Issue 6 (29th April 2019) - Gu, Hai-Ou; Sun, He; Wang, Fangyue; Ge, Can; Zhou, Taofa
Abstract : An isobaric interference correction model was proposed for the in situ Hf isotopic analysis of zircons with high Yb/Hf ratios using LA-MC-ICP-MS. Abstract : Isobaric interference correction is essential for the precise in situ Hf isotopic measurement of zircons; however, there is difficulty in doing a proper interference correction for zircons with high Yb/Hf ratios. In most of the current models, a model to determine the "natural" Yb isotopic composition is needed to fit the 176 Hf/ 177 Hf ratios of standard zircons to "true" values (measured by solution-MC-ICP-MS or ID-TIMS methods). In this study, solution doping experiments and laser ablation-multi-collector-ICP-mass spectrometry (LA-MC-ICP-MS) studies were performed. Solution doping experiments showed that β Yb and β Yb/ β Hf directly measured from samples can vary greatly with the intensity of Yb, and therefore are not good options for interference corrections. However, ( β Yb/ β Hf)c, which is calculated from samples with high Yb/Hf ratios by fixing the calibrated 176 Hf/ 177 Hf values to the "true" values, is proven to be a reliable approach for Yb interference correction. Therefore, a new isobaric correction model is proposed in this study for the in situ Hf isotopic analysis using the LA-MC-ICP-MS methodology for zircons, especially for those with a high Yb/Hf ratio. With the proposed model, the determination of the "natural" Yb isotopic composition is no longer necessary. In addition, this proposed model shows no discrimination to the Yb/Hf ratios and therefore can be widely used in most laboratories, especially for those with newly set-up instruments. The lower limit of the 180 Hf intensity is ∼1 V by our new model so that meaningful 176 Hf/ 177 Hf ratios and <1.5 ε unit internal errors can be achieved simultaneously. A ∼3 month monitoring for standard zircons showed that the long-term accuracy error is lower than 2 ε units (to referenced values).